Effect of N-acetylcysteine for the treatment of otitis media with effusion - Fatih Boztepe, Osman; Gün, Taylan; Erdem Gür, Özer; Fatih Karakuş, Mehmet; Bilal, Nagihan; Nedim Arda, Hasan (ENT Updates, 2014)
Objective: To show the efficacy of mucopeptid breaking agent N-acetylcysteine on the treatment of otitis media with effusion. Methods: A total of 64 patients who were admitted to our clinic and diagnosed otitis media with effusion were included in the study. The study group of 33 patients were administered antibiotics, decongestants, and N-acetylcysteine. The control group was treated with only antibiotics and decongestants. Both groups of patients were examined with a low-frequency probe tone (226 Hz) device before, one month, three months and 6 months after the treatment. Tympanometric and pure tone audiometric examination of the patients were performed. Results: At the end of the first month, recovery rates of the left and right ears in the study and control groups were 66 and 72% vs. 13 and 22%, respectively. At sixth month, recovery rates for the left and right ears in the study group were 91 and 94%, respectively, while the corresponding recovery rates were 48 and 55% in the control group. Conclusion: N-acetylcysteine can be used in the treatment of otitis media with effusion as a medical agent. However, studies on more patients are needed to evaluate the efficacy and long-term effect of N-acetylcysteine on otitis media with effusion.